Risk and Management of Intracerebral Hemorrhage in Patients with Bleeding Disorders - Dorgalaleh, Akbar; Farshi, Yadolah; Haeri, Kamand; Ghanbari, Omid Baradarian; Ahmadi, Abbas (Seminars in Thrombosis and Hemostasis, 2022)
Intracerebral hemorrhage (ICH) is the most dreaded complication, and the main cause of death, in patients with congenital bleeding disorders. ICH can occur in all congenital bleeding disorders, ranging from mild, like some platelet function disorders, to severe disorders such as hemophilia A, which can cause catastrophic hemorrhage. While extremely rare in mild bleeding disorders, ICH is common in severe coagulation factor (F) XIII deficiency. ICH can be spontaneous or trauma-related. Spontaneous ICH occurs more often in adults, while trauma-related ICH is more prevalent in children. Risk factors that can affect the occurrence of ICH include the type of bleeding disorder and its severity, genotype and genetic polymorphisms, type of delivery, and sports and other activities. Patients with hemophilia A; afibrinogenemia; FXIII, FX, and FVII deficiencies; and type 3 von Willebrand disease are more susceptible than those with mild platelet function disorders, FV, FXI, combined FV–FVIII deficiencies, and type 1 von Willebrand disease. Generally, the more severe the disorder, the more likely the occurrence of ICH. Contact sports and activities can provoke ICH, while safe and noncontact sports present more benefit than danger. An important risk factor is stressful delivery, whether it is prolonged or by vacuum extraction. These should be avoided in patients with congenital bleeding disorders. Familiarity with all risk factors of ICH can help prevent occurrence of this diathesis and reduce related morbidity and mortality.
Keywords: intracerebral hemorrhage; congenital bleeding disorders; morbidity; mortality